Report of ciliate-bryozoan-crustacean hyperepibiosis on crab (Decapoda: Brachyura) from west coast of India, Arabian Sea - Chatterjee, Tapas; Dovgal, Igor; Vieira, Leandro M.; Dutta, Arpita; Nanajkar, Mandar (Zootaxa, 2020)
Epibiosis is a common phenomenon, found in different taxa of aquatic animals. This relationship could occur as hyperepibiosis, when a basibiont being also an epibiont, providing a stable substrate for the hypersymbiont. Here we reported a ciliate-bryozoan-crustacean hyperepibiosis in Mandovi River mouth, Goa, West coast of India. We provided descriptions and characterization of the crab Atergatis sp., serving as basibiont for the bryozoan Triticella pedicellata (Alder, 1857), in turn colonized with (hyperepibionts) the ciliates Paracineta saifulae (Mereschkowsky, 1877) and Cothurnia ceramicola Kahl, 1933. Paracineta saifulae and Cothurnia ceramicola are reported here for first time from the Indian Ocean.